2023
DOI: 10.3390/systems11030159
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Fuzzy Structured Methodology for Performance Evaluation of High Schools in a Group Decision-Making Problem

Abstract: Evaluating and ranking schools are noteworthy for parents of students and upstream institutions (in Iran, the Ministry of Education). In this process, quantitative criteria, including educational activities, human resources, space and equipment, and administrative-financial indicators, are commonly investigated. This process is carried out only by the upstream institutions and the view of the system from the perspective of another stakeholder, namely, the students’ parents, are ignored and qualitative-judgment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Beberapa penelitian seperti bagaimana mengevaluasi efektivitas metodologi keamanan yang sangat efektif dalam layanan kesehatan digital dengan mengintegrasikan keamanan data dengan strategi manajemen yang ada [11], evaluasi teknologi bus berbasis bahan bakar yang sesuai di India [12], evaluasi kinerja sekolah menengah atas dalam masalah pengambilan keputusan kelompok [13].…”
Section: Tinjauan Pustakaunclassified
“…Beberapa penelitian seperti bagaimana mengevaluasi efektivitas metodologi keamanan yang sangat efektif dalam layanan kesehatan digital dengan mengintegrasikan keamanan data dengan strategi manajemen yang ada [11], evaluasi teknologi bus berbasis bahan bakar yang sesuai di India [12], evaluasi kinerja sekolah menengah atas dalam masalah pengambilan keputusan kelompok [13].…”
Section: Tinjauan Pustakaunclassified
“…Then, utilizing The Analytic Hierarchy Process (AHP) and Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS), they computed the subcriteria significance and the rating according to the experts' ideas. The sensitivity analysis findings indicated that ignoring the system's opinions from other stakeholders can distort the results [82]. As seen, wicked problems have been less considered in such hybrid methodologies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The role of business units in the community has recently undergone immense changes, to the point that business units are expected to increase their earnings and hold themselves accountable to their community [50]. A mutual relationship has thus emerged between the business unit and the community [51].…”
Section: Research Background and Hypothesis Developmentmentioning
confidence: 99%